2015
DOI: 10.1007/s10935-015-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Efficacy for Exercise and Improved Nutrition Fostered by Increased Self-Regulation Among Adults With Obesity

Abstract: Behavioral theory suggests that treatments that increase participants' use of self-regulatory skills and/or their feelings of ability (self-efficacy) will improve exercise and nutrition behaviors. In addition, psychosocial factors associated with increased exercise may carry over to improved eating. Self-regulation might enhance self-efficacy through feelings of ability to manage barriers to maintaining weight-loss behaviors. Sedentary adults with severe or morbid obesity (M age = 43 years; M BMI = 40.1 kg/m(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…This is valuable given that completing moderate amounts of regular exercise can reportedly positively influence mood, self-efficacy, and use of self-regulatory skills (e.g. cognitive restructuring; stimulus control) – three theory-based factors shown to be key predictors of controlled eating and weight-loss success [15, 50]. Yet, we saw no effect of the exercise alone intervention (225 mins/wk.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is valuable given that completing moderate amounts of regular exercise can reportedly positively influence mood, self-efficacy, and use of self-regulatory skills (e.g. cognitive restructuring; stimulus control) – three theory-based factors shown to be key predictors of controlled eating and weight-loss success [15, 50]. Yet, we saw no effect of the exercise alone intervention (225 mins/wk.…”
Section: Discussionmentioning
confidence: 84%
“…Group-based behavioral weight loss has been shown to reduce binge eating frequency in adults with obesity and binge eating disorder [12], while “spill over” and indirect effects of exercise have been observed on improvements in emotional eating among women with obesity [13, 14]. These changes were, at least in part, attributable to generalization of self-regulation and self-efficacy changes from an exercise context to an eating context [15]. A recent meta-analysis showed no effect of dietary weight loss on psychological stress [16]; however favorable changes in perceived stress, depression and social support have been reported in weight loss and exercise interventions, including among participants of the Nutrition and Exercise in Women (NEW) trial [17] examined in the present study, and could play a mediating role between lifestyle changes and eating behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Selfefficacy is defined as the individual's confidence in their ability to achieve a targeted behaviour (Baranowski & Hearn, 1997). For example, higher self-efficacy has been linked to greater weight loss, and healthier eating among adults and youth (Anderson-Bill, Winett, & Wojcik, 2011;Anderson, Winett, & Wojcik, 2007;Annesi, Johnson, & McEwen, 2015;Fitzgerald, Heary, Kelly, Nixon, & Shevlin, 2013;Larsen, McArdle, Robertson, & Dunton, 2015). Outcome expectation is defined as what the individual expects to happen if they modify their behaviour (Baranowski & Hearn, 1997).…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…17 Indeed, some initial studies have shown that within the context of WMPs, self-efficacy developed for PA can be carried over to self-efficacy for healthy eating. 9,17,26,39 Therefore, there is a need to better understand coaction both at the psychological and behavioral levels 40 so that researchers can design more effective, long-lasting WMPs that address each behavior when it is most appropriate within the course of treatment.…”
Section: Purposementioning
confidence: 99%